To determine the knowledge levels of hemodialysis nurses about hepatitis C virus transmitting ways and prevention methods [Hemodiyaliz ünitesi hemşirelerinin hepatit C hakkindaki bilgi düzeyleri] - (:unkn) unknown (My University, 2004)
This definitive analytical study is carried out at 13 hemodialysis ünits in İstanbul which accepted to participate. 119 hemodialysis nurses answered 30 questions from our study questinnaires. For statistical analysis, chi-square, Student's t- test, one way variance analysis and Fisher's exact chi-square tests were used. Nearly half (46.2%) of the responders were 28-37 years old. Half of them (50%) was married, and 52.1% of the nurses had preliminary education degree. A substantial proportion of them (30.3%) have been working for 5 to 8 years. The levels of knowledge on hepatitis C virus was found to be 'good' (42.9%) and 'very good' (39.5%). None of them had 'poor' grade. According to the level of knowledge on hepatitis C virus infection, significant difference was present between the age and the level of the working experience of the groups (p<0.05). Hepatitis C virus positive needle puncture was significantly different among ages and the levels of working experience of the groups. Although participants with or without needle puncture accidents had demonstrated significantly different laboratory results afterwards, (p<0.01), the rates of hepatitis C infection and the number of diagnostic tests performed differed widely between these two groups (p>0.05). Knowledge levels of hemodialysis nurses about the transmission and prophylaxis of hepatitis C virus infection was found to be sufficient.